Development of LT-HSC-Reconstituted Non-Irradiated NBSGW Mice for the Study of Human Hematopoiesis In Vivo - Adigbli, George; Hua, Peng; Uchiyama, Masateru; Roberts, Irene; Hester, Joanna; Watt, Suzanne M.; Issa, Fadi (Frontiers in Immunology, 2021)
Humanised immune system (HIS) mouse models are useful tools for the in vivo investigation of human haematopoiesis. However, the majority of HIS models currently in use are biased towards lymphocyte development and fail to support long-term multilineage leucocytes and erythrocytes. Those that achieve successful multilineage reconstitution often require preconditioning steps which are expensive, cause animal morbidity, are technically demanding, and poorly reproducible. In this study, we address this challenge by using HSPC-NBSGW mice, in which NOD,B6.SCID IL-2r-/-KitW41/W41 (NBSGW) mice are engrafted with human CD133+ haematopoietic stem and progenitor cells (HSPCs) without the need for preconditioning by sublethal irradiation. These HSPCs are enriched in long-term haematopoietic stem cells (LT-HSCs), while NBSGW mice are permissive to human haematopoietic stem cell (HSC) engraftment, thus reducing the cell number required for successful HIS development. B cells reconstitute with the greatest efficiency, including mature B cells capable of class-switching following allogeneic stimulation and, within lymphoid organs and peripheral blood, T cells at a spectrum of stages of maturation. In the thymus, human thymocytes are identified at all major stages of development. Phenotypically distinct subsets of myeloid cells, including dendritic cells and mature monocytes, engraft to a variable degree in the bone marrow and spleen, and circulate in peripheral blood. Finally, we observe human erythrocytes which persist in the periphery at high levels following macrophage clearance. The HSPC-NBSGW model therefore provides a useful platform for the study of human haematological and immunological processes and pathologies.